FROM TOURISM TO GLOBAL RECOGNITION: ELEVATING SABAHAN BRANDS THROUGH TOURIST INFLUX - Wuxiao; Suddin Lada; Faeroz Madli; Zhangyang; Rahmi; Ika Febrilia, (Malaysian Journal of Business and Economics (MJBE), 2024)
This paper investigates the role of Sabah's tourism industry in promoting local brands on a global scale, particularly in the post-pandemic landscape where tourism is experiencing significant growth. Sabah, known for its natural beauty and diverse cultural heritage, has seen a notable rise in tourist arrivals, with over 2.5 million visitors recorded in 2023 and a projected 3 million for 2024. The tourism sector’s contribution to Sabah's economy is substantial, not only in revenue generation but also in creating employment opportunities and fostering local entrepreneurship. The study focuses on the concept of tourism branding, highlighting how Sabah can leverage its indigenous culture, biodiversity, and eco-tourism offerings to build a strong and distinctive "Sabahan" brand. This brand identity can differentiate the region from other destinations while promoting sustainable tourism practices. Through an analysis of the economic impact of tourism on local businesses, branding strategies for local products, and the unique opportunities offered by Sabah’s cultural and natural resources, the paper discusses how local businesses can overcome challenges and capitalize on tourism-driven growth. The study also explores the spillover effects of tourism across sectors such as agriculture, hospitality, and transportation, emphasizing the importance of an integrated approach to regional economic development. The paper concludes by offering recommendations for enhancing Sabah’s global brand visibility, suggesting that a well-executed tourism branding strategy could position Sabah as a premier destination for eco-conscious and culturally engaged travelers. The study underscores the potential of tourism as a driver of sustainable economic development and cultural preservation, creating a positive feedback loop between regional branding and tourist influx.